2014
DOI: 10.1128/aac.01932-13
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Experimental Azithromycin Cream for Prophylaxis of Tick-Transmitted Lyme Disease Spirochete Infection in a Murine Model

Abstract: As an alternative to oral prophylaxis for the prevention of tick transmission of Borrelia burgdorferi, we tested antibiotic cream prophylactic formulations in a murine model of spirochete infection. A 4% preparation of doxycycline cream afforded no protection, but a single application of 4% azithromycin cream was 100% protective when applied directly to the tick bite site at the time of tick removal. Indeed, the azithromycin cream was 100% effective when applied at up to 3 days after tick removal and protected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The most common routes of antibiotic administration are oral administration and intravenous injection. As an alternative approach, the topical application of 4% azithromycin cream was tested (Piesman et al 2014). The result of the study showed that azithromycin was highly efficient when applied topically at the sites of tick bites in mice (Piesman et al 2014).…”
Section: On-demand Treatment Strategiesmentioning
confidence: 99%
“…The most common routes of antibiotic administration are oral administration and intravenous injection. As an alternative approach, the topical application of 4% azithromycin cream was tested (Piesman et al 2014). The result of the study showed that azithromycin was highly efficient when applied topically at the sites of tick bites in mice (Piesman et al 2014).…”
Section: On-demand Treatment Strategiesmentioning
confidence: 99%
“…10 Azithromycin is a potential antibiotic agent for prophylactic topical use. 47,48,49 Guidelines are conflicting. CDC 8 recommends according to the Infectious Disease Society of America (IDSA) guidelines for the treatment of Lyme disease.…”
Section: Conflictingmentioning
confidence: 99%
“…The prophylactic application of an antibiotic cream is also controversial. Animal studies with azithromycin cream reveal a good prophylactic efficacy [ 169 ], [ 170 ]. Placebo-controlled studies on the effectiveness in humans have yet to be published.…”
Section: Prophylaxismentioning
confidence: 99%